Moral Education of KH. Abdullah Zain Salam - Iis Nur Juwariyah (Santri: Journal of Pesantren and Fiqh Sosial, 2021)
Pesantren and priest have formed lots of Islamic scholars with high wisdom and glorious moral. Thoughts and actions of priest are able to explain how moral education should be done for students. This research aims to explain the thoughts of KH. Abdullah Zain Salam (Mbah Dullah) children moral education, the charismatic priest from Kajen, Margoyoso, Pati. Through the research of literature and interviews, the results obtained that Mbah Dullah children moral education is seen on how the methods of education which applied against children and students. The method applied is based on the teachings of Islamic religion and works of muslim scholars such as Al-Ghazali. Children moral education is carried out by way of: giving charity intended for children, self-reliance, discipline, affection, love of Qur'an, pray together with children, and bind the child’s inner with prayers.